Changes in physical fitness, muscle damage and cognitive function in elite rugby players over a season - Karamti, M. H.; Zouhal, H.; Bousselmi, M.; Darragi, M.; Khannous, H.; Hmid, A. B.; Zamali, I.; Ahmed, M. B.; Laher, I.; Granacher, U.; Moussa, A. Z. B. (Sports, 2024)
This study proposes to monitor the physical, immune and cognitive responses and adaptations of elite rugby players throughout the season based on the loads performed. Anthropometric measurements, physical fitness tests (e.g., muscle strength and power, linear and change-of-direction speed, cardiorespiratory fitness) and analyses of serum concentrations of markers of muscle damage (creatine kinase [CK] and lactate dehydrogenase [LDH]) and brain-derived neurotrophic factor (BDNF) were carried out over a sporting season (24 weeks) for 17 elite rugby players (10 forwards and 7 backs) aged 18.91 ± 0.76 years. The physical fitness test results show improvements in the performance of both forwards and backs over the season (p < 0.05), with an advantage for backs compared with forwards in most tests (p < 0.05). Muscle damage markers decreased at the end of the season compared with the baseline levels for forwards (p < 0.05). CK levels were unchanged for the backs, but there were increased LDH concentrations at the end of the season compared with baseline (p < 0.05). Serum BDNF levels decreased for the total group between the second and third sampling (p < 0.05). The muscular and physical capacities of rugby players differ according to their playing position. Immune responses and adaptations, as well as BDNF levels, vary throughout the season and depend on the physical load performed.